Analisis Kinerja Instansi Pemerintah Berdasarkan Indikator Kinerja (Kajian Dalam Manajemen Publik) - Yummil Hasan (Universitas Islam Negeri Imam Bonjol Padang, 2014)
The performance can be described as an assessment of the ability of an organization in achieving goals. Performance assessment can be used to measure the activities of a company or organization in the achievement of goals and also as material for future improvement. Performance can also mean job performance, achievements holding something. Organizational performance is a performance and implementation process in which organizational goals to be achieved. In the context of this assessment, the definition of performance is to see to what extent the achievements in the achievement of the performance of government agencies in achieving the goals set based on performance indicators. Thus, performance measurement is a useful tool in efforts to achieve the objectives, performance measurement can be done through the process of assessment of the achievement of objectives and performance measurement can provide an objective assessment in management decisions. Performance measurement can help to increase quality and lower costs arising from government activities